Performance indicators for public private partnership (PPP) projects in Malaysia - Mohamad, Rosnani; Ismail, Suhaiza; Mohd Said, Julia (Emerald Group Publishing Ltd., 2018)
Purpose The purpose of this paper is twofold: first, to identify the important performance indicators used in assessing public private partnership (PPP) performance in terms of the two aspects of PPP which are “financing and markets” and “innovation and learnings”; and second, to investigate the differences in the perception between public and private sectors on the importance of performance indicators in terms of the two aspects of PPP.